2011
DOI: 10.4161/bbug.2.2.14433
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to produce succinic acid at a low pH?

Abstract: Bio-based succinate is still a matter of special emphasis in biotechnology and adjacent research areas. The vast majority of natural and engineered producers are bacterial strains that accumulate succinate under anaerobic conditions. Recently, we succeeded in obtaining an aerobic yeast strain capable of producing succinic acid at low pH. Herein, we discuss some difficulties and advantages of microbial pathways producing "succinic acid" rather than "succinate." It was concluded that the peculiar properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…The use of a three-stage pH-shift technology during the growth and the biosynthesis phases is a principal approach for the development of highly effective and environmentally friendly processes of the α-ketoglutaric acid production. In this case, the calculated value of KOH expenditure was only 250 g per 1 kg of SA, while Yuzbashev et al (2011) reported that for the production of 1 ton of succinate with the use of bacteria, about half a ton of alkali (KOH) needs to be added to maintain neutral pH. According to literature data, the yeast Y. lipolytica can efficiently grow in a wide range of pH and produce practically valuable metabolites at low pH values (Zinjarde 2014).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The use of a three-stage pH-shift technology during the growth and the biosynthesis phases is a principal approach for the development of highly effective and environmentally friendly processes of the α-ketoglutaric acid production. In this case, the calculated value of KOH expenditure was only 250 g per 1 kg of SA, while Yuzbashev et al (2011) reported that for the production of 1 ton of succinate with the use of bacteria, about half a ton of alkali (KOH) needs to be added to maintain neutral pH. According to literature data, the yeast Y. lipolytica can efficiently grow in a wide range of pH and produce practically valuable metabolites at low pH values (Zinjarde 2014).…”
Section: Discussionmentioning
confidence: 85%
“…This stage made up 60-70 % of the product cost (Zeikus et al 1999). It is considered that the promising process should imply the fermentation without any titration agent or with its limited use where the free SA is the main product (Yuzbashev et al 2011). However, the traditional producers of SA, bacteria A. succiniciproducens, A. succinogenes, M. succiniciproducens, recombinant strains of E. coli, and C. glutamicum, should be cultivated at neutral pH, since at lower pH (5-6), significant amounts of by-products (acetate, formate, ethanol, and others) are accumulated (Zeikus et al 1999;Carole et al 2004;Werpy et al 2006;McKinlay et al 2007;Bechthold et al 2008;Bozell and Petersen 2010;Cheng To maintain optimal pH value, it is necessary to add KOH, NaOH, and other bases which react with SA; as a result, SA salts are produced rather than the desired free SA; therefore, additional stage of medium acidifying was required before the SA extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These four companies plan to produce SA in excess of 150,000 tons per annum by the end of 2015 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae, or other yeasts such as Yarrowia, can thrive under slightly acidic conditions and methods for their metabolic engineering are well established [33]. S. cerevisiae is an industrial organism capable of fermentative production and tolerance of high sugar concentrations.…”
Section: Succinic Acid-producing Microorganismsmentioning
confidence: 99%